Strengthening Simple Entrepreneurship Culture for Low-Grade Students - Husaini, Mhd Novedy; Azwanda, Yuri El Hanif; Yusuf, Syahril; Hartono, Hartono (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study examines the strengthening of simple entrepreneurial culture among lower-grade students at SD IT Al Amin Tarai Bangun as an early effort to develop independence, communication skills, and responsibility. The research focuses on how experiential-based entrepreneurial activities such as mini-selling, simple market day events, handicraft production, and caring for a mini garden are implemented within daily classroom routines. The study aims to describe the forms of activities conducted, analyze how teachers manage and facilitate these practices, and identify the initial impact on students’ character development. A descriptive qualitative method was employed, involving classroom observations, in-depth interviews with the principal and grade 1–2 teachers, and documentation. The findings indicate that entrepreneurial activities have been naturally integrated into classroom practices and positively influence students’ confidence and independence, although the program has not yet been supported by a structured curriculum or formal guidelines. This research contributes to the field of primary education management by demonstrating that simple and developmentally appropriate activities can effectively initiate entrepreneurial habituation when carried out consistently and supported by school management. These results are significant as they offer a practical foundation for developing sustainable models of simple entrepreneurship programs in elementary schools